Effects of tenectomy of the medial head of the deep digital flexor on the hindlimbs of healthy horses - Pizzigatti, D.; Raffael, L. A. [UNESP]; Rodrigues, C. A. [UNESP]; Watanabe, M. J. [UNESP]; Alves, A. L. G. [UNESP]; Barbosa, L. [UNESP]; Hussni, C. A. [UNESP] (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2019)
The tenectomy of the medial head of the deep digital flexor (TMHDDF) is a minimally studied surgery used in cases of dorsal subluxation of the proximal interphalangeal joint of the hindlimb in horses. The TMHDDF was evaluated in six healthy horses by the degree of lameness, perimeter of the surgical site, the angle of the distal articular joints, and the linear and angular measures of the hoof. Thus, TMHDDF of the right hindlimb was performed and the contralateral limb was used as a control. Both, right and left limbs were evaluated before surgery, as well as at 15, 30, and 60 days after surgery aiming to evaluate the effects of the surgical procedure in healthy limbs. Data were compared by analysis of variance regarding days and limbs. Values below the significant level (P< 0.05) were analyzed using the Tukey's test. TMHDDF caused a mild increase of the toe length and the height of lateral heel (0.2cm in both), as well as a decrease of the angle of the proximal interphalangeal joint (2 degrees) when comparing the left hindlimb to the right hindlimb, 30 and 60 days after surgery. Overall, TMHDDF did not cause significant changes in the evaluated variables up to the 60 days of surgery.
Keywords: tenectomy; medial digital flexor tendon; pastern joint; arthrogoniometry